The Utilization of Coconut Fiber and Marble Waste with Mechanical Tests - Anwar, Ihsan; Fitriadi, Nuzuli; Afriana, Winda; Ben, Hasbaini (LEMBAGA KAJIAN PEMBANGUNAN PERTANIAN DAN LINGKUNGAN (LKPPL), 2023)
The area of coconut plantations in South Aceh Regency was 6839 Ha, out of the total number of sub-districts in South Aceh. South Kluet District was the area with the largest coconut plantation area compared to other districts, reaching 1433 Ha. Coconut coir fiber was usually used for household equipment, such as floor brooms, doormats and rope. Coconut farmers rarely process coconut husks, and after harvest, they just leave the coconut husks piled up under the coconut trees until they rot. In this research, coconut fiber waste was used as reinforcing fiber for composite materials. The aim of this research was to be determined the mechanical strength of marble waste composites mixed with resin and reinforced with coconut fiber. The composition tests carried out were: 85 : 10 : 5, 80 : 10 : 10, 90 : 7.5 : 2.5, and 80 : 12.5 : 7.5. The test carried out on each test specimen composition was a tensile test. From the results of the tests carried out on the test specimens, the maximum stress was found in the composition: (85: 10: 5) 85% Resin, 10% Marble, 5% Coconut Fiber with an average maximum stress value of 29.44827586 N /m2 and the average modulus of elasticity is 0.2415123283 N/m2.